COOPERATION PROBLEMS OF THE STATE AND BUSINESS IN THE FIGHT AGAINST THE SHADOW ECONOMY AND CORRUPTION - R. Akalovich (Publishing House of the State University of Management, 2016)
In the article there are marked difficulty fighting corruption in government agencies, are considered the interests of business structures in the implementation of anti-corruption policy. The characteristic of the shadow capital of corrupt subjects of public relations as a factor of occurrence of unequal conditions in the market is done. The positive and negative points of possible participation of commercial entities in anti-corruption activities of the state are analyzed. Proposals to empower the business community with additional authorities that can help reduce the level of corruption are done.